Pengaruh Kombinasi Magnesium Stearat dan Talkum sebagai Lubrikan terhadap Profil Disolusi Tablet Ibuprofen - Syofyan Syofyan; Tri Yanuarto; Maria Dona Octavia (Jurnal Sains Farmasi & Klinis, 2015)
A research has been conducted on the combination effect of magnesium stearate and talc as a lubricant to the dissolution profile of Ibuprofen tablets. Of the three formulas made Ibuprofen tablets with wet granulation method. Evaluation of tablets include uniformity of size, weight uniformity, tablet hardness, disintegration, friability of tablets, assay and dissolution. Results of dissolution percentage was done up to 60 indicated that the dissolution the average was 95,72%, 97,65% and 99,93% consecutively for F I, F II and F III. In addition, result of the dissolution efficiency up to 60 minutes for each formula was 82,10%, 87,58%, and 90,76%. According to the dissolution of the data, formula III which had the highest dissolution results compared to formula I and formula II, which likely due to the ratio of the combination of magnesium stearate and talc as a lubricant smaller levels of magnesium stearate.